Optimized Stirred Reactor for Enhanced Particle Dispersion. Issue 4 (4th March 2016) - Wang, Steven; Jiang, Mo; Ibrahim, Shaliza; Wu, Jie; Feng, Xin; Duan, Xiaoxia; Yang, Zhao; Yang, Chao; Ohmura, Naoto
Abstract: Homogeneous dispersion of particles is crucial for many processes where the reaction rate is highly dependent on relative rates of mixing or degree of homogenization. These processes include crystallization, polymerization, and some mineral‐refining processes. Complete particle dispersion in high‐concentration slurries is researched experimentally and numerically. Computation fluid dynamics results suggest that cloud height is an excellent indicator for mixing homogeneity, and energy efficiency can be enhanced by removing baffles over a range of solids concentrations under the complete dispersion condition. The power required to maintain a high cloud height in a stirred tank can be predicted via a simple power number analysis. The proposed unbaffled design can be potentially beneficial to some industrial processes like crystallization. Abstract : Homogeneous dispersion of particles is critical for many processes. The cloud height served as criterion to evaluate suspension homogeneity. Particle distributions were numerically studied under baffled and unbaffled conditions. Homogenization power can be predicted via a simple power number analysis. The proposed design has great potential for industrial processes like crystallization.